Operational outages in large value payment systems - Mills, David (Henry Stewart Talks, 2010)
Large value payment systems (LVPS) are important for the financial system, The need for reliable liquidity sources to facilitate settlement, Operational outages can negatively impact a LVPS, Operational outages are costly, Example of an operational outage, Factors that determine the impact of operational outages, Network topologies, Participant's strategic behavior, Participants, operators and central banks can take steps to mitigate an outage's impact, Fedwire during 9/11/2001, Federal reserve response to 9/11/2001, Federal reserve liquidity measures, Multi-bank outages